The meaning of expenditure actually incurred in the context of share-based payments for trading stock or services rendered - Nguta, Mbulelo (Rhodes University, Faculty of Commerce, Department of Accounting, 2015)
Section 11(a) of the Income Tax Act 58 of 1962 entitles taxpayers to a deduction in respect of expenditure actually incurred, provided that all the other requirements of section 11 and section 23 of the Act have been met. A company may issue its own shares, credited as fully paid up, as a payment for trading stock or services rendered, as was the case in C:SARS v Labat Africa (2011) 74 SATC 1. The question that was raised by this decision is whether the issue of shares constitutes "expenditure" as contemplated in section 11(a) of the Act. It is trite that a share in a company is a bundle of rights which entitle the holder to dividends when declared and to a vote in shareholders' meetings and that a share does not come into the hands of a shareholder by way of transfer from the company, but is rather created as a bundle of rights for him in the company. In C: SARS v Labat Africa, the Supreme Court of Appeal decided that to issue shares as a payment for goods is not expenditure as contemplated in section 11(a) of the Act. The Act does not define "expenditure" . It has been interpreted in certain cases as a payment of money or disbursement, while it has been interpreted as the undertaking of a legal obligation in other cases. The Labat Africa case has been criticised for its interpretation of expenditure on the grounds that it is contrary to the principle that "actually incurred" does not mean "actually paid" . This research has argued that, in the context of the Labat Africa case, which related to an issue of shares in payment for goods, Harms AP's judgment was concerned with showing why a share issue is not expenditure. He could not have intended to deny a deduction to transactions such as credit purchases.
Keywords: South African Revenue Service; Labat Africa; Stocks -- Taxation -- Law and legislation -- South Africa; Income tax deductions for expenses; Income tax -- Accounting -- Law and legislation -- South Africa; Actions and defenses